Pengaruh Media Sosial Instagram dalam Membentuk Konsep Diri Siswa SMP - Saputro, Fathan Faris (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The younger generation is increasingly using social media, especially Instagram. The user's identity appears to be reflected in the content produced. The aim of this research is to examine how Muhammadiyah 20 Solokuro Middle School students develop a sense of self through Instagram. This research uses the Uses and Gratifications theory and qualitative descriptive methods by means of observation, interviews and collecting documentation as secondary data. The findings of this research indicate that students at SMP Muhammadiyah 20 Solokuro created a self-concept for two reasons: to fulfill their need for social integrity (a social integrative need) and their need for cognitive stimulation (a cognitive need). In addition, the informants displayed three characteristics of self-concept: self-awareness, self-defense, and differentiation between real and ideal self, true and false self. Likes, comments and the information they post are some of the elements that can influence how people perceive themselves. They don't really care about their followers. Because Instagram users do not meet in person, informants feel more comfortable interacting on the application than when chatting face to face.